Letter (copy) : Ray Cox Memorial - Citrine, Walter, 1887-1983
042-0137-001 WMC/EAB/829 INTERNATIONAL. 8th June 1937. Mr. G. Stolz, International Federation of Trade Unions, 9 Avenue D'Orsay, PARIS. VII. Dear Comrade Stolz, RAY COX MEMORIAL You will remember we wrote you on 14th April last regarding certain apparatus to be purchased to which was to be affixed a plaque stating that it is the Ray Cox Memorial. I shall be glad if you will be good enough to let me know whether you are yet in a position to let me have a photograph of this memorial in order that we may provide some visual evidence to the subscribers. Yours sincerely, General Secretary. 292/946/42/137